Onboarding Experience in Large Tech Organizations in Tier I Cities of India Post-Pandemic & Its Impact on Employee Turnover - Malik, Megha (Digital Repository of Theses, 2025)
Purpose: This study aims to analyze the onboarding experience in large tech organizations located in Tier I cities of India post the COVID-19 pandemic, with a specific focus on how managerial and peer support affects employee turnover rates. Employing a Quantitative method approach, this research includes surveys of new employees within few organizations to understand their onboarding experiences and support systems. Quantitative data analysis is conducted to provide a comprehensive understanding of the subject. Preliminary findings suggest that effective managerial and peer support significantly enhances the onboarding experience, reducing stress and improving job satisfaction among new hires, which subsequently lowers turnover rates. However, the lack of structured support mechanisms during remote onboarding led to higher levels of disengagement and turnover. The findings underscore the importance of robust managerial and peer support systems in enhancing the onboarding experience in large tech organizations. The study recommends implementing structured support programs to facilitate better employee integration and retention, especially in the context of hybrid or remote work environments.